The Nonequivalence of High School Equivalents - Cameron, Stephen V.; Heckman, James J. (Journal of Labor Economics, 1993)
This article analyzes the causes and consequences of the growing proportion of high-school-certified persons who achieve that status by exam certification rather than through high school graduation. Exam-certified high school equivalents are statistically indistinguishable from high school dropouts. Whatever differences are found among exam-certified equivalents, high school dropouts and high school graduates are accounted for by their years of schooling completed. There is no cheap substitute for schooling. The only payoff to exam certification arises from its value in opening postsecondary schooling and training opportunities, but completion rates for exam-certified graduates are much lower in these activities than they are for ordinary graduates. Copyright 1993 by University of Chicago Press.